Do founding families downgrade corporate governance? The roles of intra-family enforcement - Fan, Joseph P.H.; Yu, Xin (Journal of Corporate Finance, 2022)
We examine whether adding more founding family members as firm owners and/or managers matters to corporate governance outcomes. Based on a sample of 1242 founder-controlled publicly traded Chinese private-sector firms, we find that more such family involvement is associated with lower volumes of related party transactions suspicious of expropriating shareholder wealth. The curtailing relation is stronger when family members own firm shares and/or serve as managers, and are more arm's-length relatives instead of immediate kin of the founders. The intra-family governance effects are stronger when firms are subject to weaker capital market disciplines or have more free cash under insider discretion. The overall evidence is consistent with founding family members' information advantages and ownership incentives making them more robust monitors of managerial decisions than other formal mechanisms, which help enforce shareholder rights in emerging markets.